How do practitioners manage decision knowledge during continuous software engineering? - Kleebaum, Anja; Paech, Barbara (Proceedings SEKE 2019, 2019)
We report on results from an interview study with 24 practitioners from 17 companies on how decision knowledge is managed during CSE.
Keine zentrale Startseite für den Artikel vorhanden, der Link führt direkt zum PDF
Gesehen am 16.12.2019